(untitled) (Prosiding Keislaman dan Sains, 2025)
The study aimed to find answers to the question of the application of risk mitigation in Islamic bank financing in the review of maqoshid sharia. The study used a qualitative method with a literature review of several existing studies. Data collection used secondary data methods obtained from journal articles, proceedings articles, books, and the internet. The research findings show that the risks of financing efforts channeled by Islamic banks are credit/financing risk, operational risk, and liquidity risk. The study results show that risk mitigation of Islamic banks in the review of maqoshid sharia is a form of carrying out religious messages, trust in managing assets, guarantees of halalness, a sense of security, and anticipation of loss of funds. The study contributes to providing input to Islamic banking actors that implementing risk management and risk mitigation before running a financing distribution business is a form of carrying out religious orders, and protection of assets.